2019
DOI: 10.1097/md.0000000000015141
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an antiadhesive agent for the prevention of intra-abdominal adhesions after radical gastrectomy

Abstract: Background: Guardix-SG is a poloxamer-based antiadhesive agent. The aim of this study was to investigate its efficacy in preventing abdominal adhesions in gastric cancer patients undergoing gastrectomy. Few clinical studies have reported that antiadhesive agent reduces the incidence of adhesion after gastrectomy. Methods: We conducted a multicenter trial from June 2013 and August 2015 in patients with gastric adenocarcinoma undergoing radical gastrectomy. Patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Mediclore has been previously demonstrated to be safe and effective in the prevention of adhesion formation after various surgical procedures [29][30][31]. A recent study reported that the use of another poloxamer-based thermo-sensitive anti-adhesion agent reduced the incidence of intestinal obstruction after radical gastrectomy for gastric cancer without increasing the risk of complications [35]. In line with the previous studies, we also demonstrated the adhesion-prevention effects and safety of Mediclore in patients who underwent benign gynecologic surgeries.…”
Section: Discussionsupporting
confidence: 89%
“…Mediclore has been previously demonstrated to be safe and effective in the prevention of adhesion formation after various surgical procedures [29][30][31]. A recent study reported that the use of another poloxamer-based thermo-sensitive anti-adhesion agent reduced the incidence of intestinal obstruction after radical gastrectomy for gastric cancer without increasing the risk of complications [35]. In line with the previous studies, we also demonstrated the adhesion-prevention effects and safety of Mediclore in patients who underwent benign gynecologic surgeries.…”
Section: Discussionsupporting
confidence: 89%
“…PEG has had positive outputs in terms of patient safety, cost-effectiveness, and level of postoperative pain 157 , 159 , 160 . Poloxamer 407 alginate has been shown to have a high level of patient safety 165 , but cost-effectiveness, and postoperative pain are unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Natural polymer based antiadhesives utilize materials such as hyaluronic acid, chitosan, and carboxymethylcellulose . A number of products showed good clinical results in abdominal surgery . Most natural polymer based products, however, are biomechanically weak and degrade too quickly to be used during tendon surgery.…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…[28][29][30] A number of products showed good clinical results in abdominal surgery. [31][32][33] Most natural polymer based products, however, are biomechanically weak and degrade too quickly to be used during tendon surgery. Such limitations have led to research regarding decellularized tissue, which are both bioactive and biomechanically stronger than classic natural polymers.…”
Section: Discussionmentioning
confidence: 99%